Einfluss von α-Methylsubstituenten auf die Triplett-Di-π-Methan-Umlagerung von Allylbenzolen - Jean-Pierre Fasel; Hans-Jürgen Hansen (CHIMIA)
The sensitized di-π-methane rearrangement of allylated benzene derivatives is strongly favoured by α-methyl substituents in the allyl side chain (Scheme 2). On the other hand, β- and γ-methyl substituents in the allyl moiety hinder or at least retard the triplett di-π-methane rearrangement. In the presence of additional α-methyl groups the rearrangement is again facilitated (Scheme 3). The triplet di-π-methane-rearrangement of 4-allyl biphenyl is also strongly influenced by α-methyl substituents (Schema 4).